Hedges and Boosters as Modality Markers: An Analysis of Nigerian and American Editorials - Oluwasola Emmanuel Ojo (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2020)
Many studies have been carried out on the use of hedges and boosters as persuasive strategies, but little is known about their employment when texts such as editorials are compared cross culturally. This study comparatively examined the employment of modality markers to express doubt and conviction in Nigerian and American editorials. Farrokhi and Emami’s (2008) classification of hedges and boosters was employed to analyze twenty editorials selected from two Nigerian newspapers and two American newspapers. Findings reveal that both sets of editorial writers made use of hedges and boosters a lot in their writings. However, lexical verbs were not employed as boosters in the analyzed editorials. The fact that the Nigerian editorial writers as ESL writers equally made great use of hedges and boosters implies that in texts such as editorials, writers from different cultures equally employ the same linguistic devices to express doubt and conviction.